Auditor Independence: Evidence from Ghanaian Polytechnics - Doe, Mawutorwu; Owusu, Frank; Koranteng, Eugene Oware; Annan, Ebenezer Mensah (Asian Journal of Social Sciences and Management Studies, 2016)
There is a perception that internal audit units (IAUs) in private and public sector organisations cannot be independent in executing their functions because the personnel of the units are on the one hand employees of their organisations and on the other hand expected to provide assurance services to management professionally. Such an outlook has the tendency to impair the credibility of IAUs as well as the professionalism of the IAU. This exploratory study examined the independence in appearance of the IAUs in selected Ghanaian polytechnics within the framework of organisational status of the IAUs, reporting line of the IAU and the power conferred on the Ghanaian public sector audit committee (AC) to ensure independence. Data was collected from the Directors of Audit (DOA) using a survey method. Results of the study suggest that the IAUs in Ghanaian polytechnics are largely independent in appearance. However, the study suggests that the Ghanaian AC has only an audit report implementation responsibility in reference to the enabling parliamentary act. The paper contributes to the auditing literature by providing some insights into the concept of auditor independence in public sector organisations within the context of national legislation and international best practice in the auditing profession.